Concerning the question of the origin and development of urinary symptoms among the patients with diabetes mellitus type 1 and 2 - E. Kuznetsova; A. Gozhenko; M. Saiensus (Journal of Education, Health and Sport)
Analyzed disorders of the kidney in 102 patients with diabetes mellitus type 1 and 2, who were hospitalized at the Odessa Regional Clinical Medical Center during 2012-2013 to take into account general clinical research, clinical diagnosis, comorbidities and complications of diabetes, as well as laboratory and instrumental methods of investigation, which included a definition HBAlc, fasting glucose and dynamics in 8.00-12.00-16.00-19.00, glycosuria and acetonuria of daily urine, complete blood count, urinalysis, liver, kidney tests, ECG, ultrasound of the abdomen and kidney.